2021
DOI: 10.1111/desc.13191
|View full text |Cite
|
Sign up to set email alerts
|

Young children form generalized attitudes based on a single encounter with an outgroup member

Abstract: The goal of the present research was to assess whether children's first interaction with a single outgroup member can significantly impact their general attitudes toward the outgroup as a whole. In two preregistered studies, 5-to 6-year-old Chinese children (total N = 147) encountered a Black adult from another country for the very first time, and they played a game together. General attitudes toward the outgroup were assessed using both implicit and explicit measures. In both studies, the interaction resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
(109 reference statements)
1
3
0
Order By: Relevance
“…Our findings build on prior evidence indicating that the same intervention can have different effects on implicit and explicit racial bias (Qian et al, 2017(Qian et al, , 2020Yu et al, 2021) and raises important questions about why providing identifying information about a single outgroup member is sufficient to reduce explicit bias but not implicit racial bias. One possible reason is that implicit measures use exemplars of the race category (e.g., individual Black faces) as stimuli, while explicit measures assess responses to race categories (e.g., Black people in general), and it may be easier for children to generalize positive attitudes from an individual to the group than from one individual to another.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings build on prior evidence indicating that the same intervention can have different effects on implicit and explicit racial bias (Qian et al, 2017(Qian et al, , 2020Yu et al, 2021) and raises important questions about why providing identifying information about a single outgroup member is sufficient to reduce explicit bias but not implicit racial bias. One possible reason is that implicit measures use exemplars of the race category (e.g., individual Black faces) as stimuli, while explicit measures assess responses to race categories (e.g., Black people in general), and it may be easier for children to generalize positive attitudes from an individual to the group than from one individual to another.…”
Section: Discussionsupporting
confidence: 80%
“…Participants were randomly assigned to a differentiation condition (N = 33, 15 girls), in which they were asked to play a 2-min coordinated movement game with four Black instructors, and/or a no-differentiation condition (N = 33, 16 girls), in which they were asked to play the same game with only one Black instructor for the same amount of time. We did not include an additional control condition with same race individuals in light of prior research documenting no effect of such interactions on implicit bias (Qian et al, 2017(Qian et al, , 2019bYu et al, 2021).…”
Section: Participantsmentioning
confidence: 99%
“…Note however that direct contact can also have unintended consequences. For example, contact can lead to more positive explicit attitudes, but more negative implicit attitudes (Yu et al, 2021): given that implicit attitudes are a predictor of behavior (Kurdi et al, 2019), it can be inferred that contact may also in some cases worsen intergroup behavior. For instance, negative (e.g., threatening) conditions or expectations can translate into negative contact, which can have detrimental effects on intergroup relations (Schafer et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Positive D scores indicate implicit gender–toy stereotype knowledge of associating boys with boy-typed toys and girls with girl-typed toys. Recent research using similar methods in the domain of race has shown that children’s D scores are not influenced by their ability to manage the task or shift between the congruent and incongruent pairings (C. Yu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%